Strategy for Fintech Applications in the Pacific Island Countries - Davidovic, Sonja (Departmental Papers; Departmental Paper ;, 2019)
The Bali Fintech Agenda highlights 12 principles for policymakers to consider when formulating their approaches to new financial technology (fintech). The agenda aims to harness the potential of fintech while managing associated risks. This paper looks at how some elements of the Bali Fintech Agenda could be used in Pacific island countries, which face significant financial-structural challenges.